Effect Of Feeding Made With Different Composition On Growth and Survival Seeds Of Barramundi (Lates calcarifer , Bloch ) - Qurnia Hardianti; Rusliadi '; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from February 2016 to March 2016 at Marine Aquaculture Development Center Batam Marine . The aim of this was to determine the effect of feeding different composition on the growth and survival of the best , and also determine the optimal composition of the artificial feed were able to increase the growth and viability of seeds of barramundi ( Lates calcarifer , Bloch ) . The method used is an experimental method by using a Complete Random Design (CRD) with 4 treatments and 3 repetitions . The treatment in this study were P1 ( Feed brand Mem ) , P2 ( Feed brand NRD 5/8 ) , P3 ( Feed brands Ms Feng Li Super ) and P4 ( Feed brands Ms Frima Feed) . The best results in this study were treated with growth P1 absolute weight ( 2.55 g ) , the absolute length (2.72 cm ) , daily growth rate (5.44%) and survival rate (91.7%) .Key words : Composition, Growth, Survival Rate, (Lates calcarifer, Bloch))